Analisis Realisasi Pajak Bumi dan Bangunan di Kecamatan Kebumen terhadap Peningkatan Pendapatan Asli Daerah Kabupaten Kebumen - Sudrajat, Rachmat Adji (Universitas Pahlawan Tuanku Tambusai, 2025)
This research aims to analyze the Land and Building Tax (PBB) realization in Kebumen District in 2025, identify factors affecting the realization rate, and formulate strategies to increase PBB revenue. The research method uses a descriptive qualitative approach with data collection techniques through documentation and secondary data analysis. The results show that the PBB realization rate in Kebumen District in 2025 has not reached the established target. Several factors affecting this realization rate include the lack of taxpayers' understanding of tax obligations, suboptimal administrative systems, and community economic factors. There are variations in realization rates among villages/sub-districts in Kebumen District, with some villages achieving targets while others remain below target. Optimization efforts that can be implemented include intensifying tax socialization, improving service quality, enhancing collection systems and procedures, and strengthening coordination between local governments and village/sub-district officials. This research provides theoretical and practical implications for developing regional fiscal policies, particularly in efforts to increase Local Own-Source Revenue through optimizing PBB collection.